Dog - Clutton-Brock, Juliet (London DK Pub., Inc, 2004)
"Discover the natural history of dogs - from wolves and jackals to family pets and show dogs"--Cover. Text and photographs highlight the evolutionary history of the dog family, their domestication, anatomy, behavior, and breeds
Includes index
3
Keywords: Canidae -- Juvenile literature; Dog breeds -- Juvenile literature; Dogs -- Juvenile literature; Working dogs -- Juvenile literature